Pickering Emulsion Transitions in 2,6-Lutidine Plus Water Critical Liquid Mixtures - Matsubara, Hiroki (Langmuir : the ACS journal of surfaces and colloids, 2020)
Silica particle (S) stabilized oil-in-water Pickering emulsions are observed in the two-phase region of the critical liquid mixture 2,6-lutidine (L) plus water (W). De-emulsification is found at temperatures below a particle wetting transition temperature Tw(R) where Tw(R) decreases toward the lower critical temperature Tc for smaller particle radii R. The presence of a Pickering emulsion transition and its dependence upon particle radius can be explained by a competition between destabilizing gravitational forces and stabilizing forces originating from the critical interfacial tension. As a corollary to these observations, the line tension τ at the three-phase SLW contact line is determined as a function of temperature